2004
DOI: 10.1128/jcm.42.1.186-192.2004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Group C and G Streptococcal Strains That Cause Streptococcal Toxic Shock Syndrome

Abstract: Twelve strains (the largest number ever reported) of group C and G 1 streptococci (GCS and GGS, respectively) that caused streptococcal toxic shock syndrome (STSS) were collected and characterized. Eleven strains were identified as Streptococcus dysgalactiae subsp. equisimilis, and one strain was identified as Streptococcus equi subsp. zooepidemicus. We found that it was the first reported case of STSS caused by S. equi subsp. zooepidemicus. Cluster analysis according to the 16S rRNA gene (rDNA) sequences reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
122
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(131 citation statements)
references
References 56 publications
6
122
1
2
Order By: Relevance
“…equisimilis strains having group A antigen rather than group C or G antigen have also been reported (Bert & Lambert-Zechovsky, 1997;Brandt et al, 1999;Katsukawa et al, 2002). Many recent studies have reported that this organism causes invasive and systemic streptococcal infections like GAS (Natoli et al, 1996;Wagner et al, 1996; Hirose et al, 1997; Kugi et al, 1998;Barnham et al, 2002;Cohen-Poradosu et al, 2004;Hashikawa et al, 2004). The organism has also been reported to cause a wide variety of human infections such as pharyngitis, cellulitis, sepsis, meningitis and endocarditis (Woo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…equisimilis strains having group A antigen rather than group C or G antigen have also been reported (Bert & Lambert-Zechovsky, 1997;Brandt et al, 1999;Katsukawa et al, 2002). Many recent studies have reported that this organism causes invasive and systemic streptococcal infections like GAS (Natoli et al, 1996;Wagner et al, 1996; Hirose et al, 1997; Kugi et al, 1998;Barnham et al, 2002;Cohen-Poradosu et al, 2004;Hashikawa et al, 2004). The organism has also been reported to cause a wide variety of human infections such as pharyngitis, cellulitis, sepsis, meningitis and endocarditis (Woo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Group C and G Streptococci are reportedly common causes of tonsillitis or pharyngitis in both adults and children in tropical countries [8,9,11] while group A is common in the temperate countries [29]. Other streptococcal groups of D, F and G isolated in this study have previously been implicated in tonsillitis [30].…”
Section: Discussionmentioning
confidence: 93%
“…The beta haemolytic streptococci group C and G have also been reported as causing acute pharyngitis but their involvement in RF and RHD is still controversial [7,8,9,10]. GAS infection is spread by droplets, thus accounting for it high transmissibility in such situations [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, some strains are found to induce α-hemolysis or no hemolysis at all, in the abovedescribed standard conditions [20][21][22]. As in the case of S. pyogenes, there exist strains of SDSE which produce oxygen-labile streptolysin O, and no streptolysin S [20,23,24]. The occurrence of such strains has been an incentive to search for media and conditions of incubation which would enhance the activity of streptolysin O [20].…”
Section: Introductionmentioning
confidence: 99%
“…Both species have antiphagocytic M protein, encoded by emm [10,35,36] and hyaluronic capsule [10,35]. There are, however, marked differences between them: SDSE, for example, lacks the whole set of genes encoding superantigens, which are mostly of phage origin (spe A, spe B, spe C, spe H, spe I, spe J, spe K, spe L, spe M, ssa, smez) [12,15,24,35,[38][39][40][41][42]. However, scarce occurrences of SDSE strains have been described, having one of those genes [32,43].…”
Section: Introductionmentioning
confidence: 99%